EEG signal classification using Particle Swarm Optimization (PSO) neural network for brain machine interfaces - Paulraj, Murugesapandian; Hema, Chengalvarayan Radhakrishnamurthy; Ramachandran, Nagarajan; Sazali, Yaacob; Abdul Hamid, Adom (Association for the Advancement of Modelling & Simulation Techniques in Enterprises (A.M.S.E.), 2009)
Link to publisher's homepage at http://www.amse-modeling.com